Proximity without Productivity : Agglomeration Effects with Plant-Level Output and Price Data - Grover, Arti; Maloney, William, F. (World Bank, Washington, DC, 2022)
Recent literature suggests that the positive impact of population density on wages, the canonical measure of agglomeration effects, is multiples higher in developing countries than in advanced economies. This poses an urban productivity puzzle because on-the-ground observations do not suggest that cities in developing countries function especially well or are conducive to enhanced productivity. This paper uses manufacturing censuses from four countries at differing levels of income that allow separating plant output quantity from prices. It shows that higher wage elasticities with respect to density are due to higher marginal costs, and agglomeration elasticities of efficiency, physical total factor productivity, are in fact far lower in developing countries. Further, congestion costs decrease with country income. Both are consistent with often low rates of structural transformation that make cities in developing countries so-called “sterile agglomerations,” which are populous but not efficient.